Ministry of Trade and Industry Decree No. 612 of the Year 2013 On Imposing An Export Duty On Certain Kinds Of Scrap and Materials = وزارة التجارة والصناعة قرار رقم 612 لسنة 2013 فى شأن رسم الصادر على بعض أنواع الخردة والخامات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.